Supercritical hydrogenolysis of fatty acid methyl esters: Phase equilibrium measurements on selected binary and ternary systems - Rovetto, Laura Jorgelina (2005)
Fatty alcohols (FOH) are industrially obtained by heterogeneous catalytic hydrogenolysis of fatty acid methyl esters (FAME). Reaction rates are strongly dependent on hydrogen concentration at the catalyst surface, which is limited by the low solubility of hydrogen and high mass-transport resistance of the liquid substrate. The addition of a supercritical solvent can bring the reactive mixture into a single phase, increasing the reaction rate by several orders of magnitude. Propane has shown to be an adequate supercritical medium for these reactions. To find the homogeneous region and to determine the most favorable process conditions, it is a prerequisite to know the phase equilibrium boundaries of the reactive mixture as the reaction proceeds. This paper reports experimental phase equilibrium data on binary and ternary mixtures of propane with the reactants and reaction products of the hydrogenolysis of methyl palmitate: methyl palmitate, hydrogen, hexadecanol and methanol. A temperature region between 300 and 450 K, and pressures up to 15 MPa were covered. A liquid-liquid-vapor region was found in the system hexadecanol + hydrogen + propane, showing retrograde behavior of the lighter liquid phase.